Can climate-smart agriculture projects be leveraged for peacebuilding? Lessons from Kaffrine, Senegal - Bioversity International and International Center for Tropical Agriculture (CIAT) (2025)
Climate-smart agriculture can boost harvests, but can it also spark community tensions? In Kaffrine, Senegal, 90% of farmers saw higher yields under the Climate-Smart Village model. Yet youths felt sidelined, smallholders feared resource capture, and 92% demanded stronger institutions. A new Guidance Note from CGIAR Climate Security explores these dynamics and introduces the CSV+ approach, which blends climate innovation with conflict sensitivity. Climate adaptation must be conflict-sensitive, or we risk trading resilience for resentment.